Pitfall prayer marks: Recognition and appropriate treatment: A case report and review of literature. Issue 1 (20th December 2019) - Fosse, Nicole; Rast, Anna C.; Kammermann, Andrea; Sonderegger, Joanna; Navarini, Alexander; Goldust, Mohamad; Brandt, Oliver; Mueller, Simon M.
Abstract: Prayer marks are asymptomatic callosities resulting from repeated, extended pressure, and friction exerted on bony prominences when praying on hard ground. A 41‐year‐old woman with ulcerative colitis treated with infliximab was referred to our clinic due to skin changes on her feet that were suspected to be drug eruptions. The patient presented several asymptomatic, hyperpigmented, and hyperkeratotic plaques over the lateral malleoli suggesting that the lesions had a mechanical cause. Further exploration revealed that the patient, a practicing Muslim, prays in a sitting position called "Julus" several times a day. After color marking, the lesions over the lateral feet left a precise imprint on the underlay when the patient was asked to imitate the praying posture—thus proving the origin of the skin lesions. We searched the database on July 31, 2019 using the terms «prayer marks» OR «prayer nodules» OR "prayer callosities." Only electronically available publications were reviewed. Recognition of prayer marks is important to avoid misdiagnosis, performance of unnecessary diagnostic procedures, and to enhance the intercultural competence of clinicians who practice in multicultural societies.